Time Variation on The Supine Position When Venipucture on Total Cholesterol Level (Jaringan Laboratorium Medis, 2023)
Laboratory internal quality assurance includes pre-analytic, analytic and post-analytic stages. The error in the pre-analytic reached 68%, 25% in the analytic stage, while in the post-analytic stage it was approximately 14%. The aim of this study to determine the effect of supine position treatment during venous puncture to the total cholesterol level of respondents at minutes 0', 10', 20'and 30'. The method used is a quasi-experimental method. Research subject are 6 STr TLM semester 3 and 5 students using the method sampling by non random sampling. There is a change of -3.2% in the 10th and 20th minutes, there is also a change of -1.6% in the 10th and -30th minutes. Statistical analysis is presented using the one-way ANOVA test, it is said that there are significant differences if the p value